A dangerous pathway? Toward a theory of special forces. Issue 4 (4th July 2019) - Finlan, Alastair
Abstract: This article explores what is considered by some to be a dangerous pathway: the development of a theory of special forces. The world is now in the third age of special forces and these secret military units are at the forefront of the use of force in international relations. This research identifies a large theory-knowledge gap concerning these military "first responders" for modern nation-states and offers a tentative theory of special forces that goes beyond traditional annihilation/attrition models of war toward a new anaphylaxis model. It makes the case that the theory pathway is not dangerous, but emancipatory.